The economics of Islamic financing guarantee scheme of Credit Guarantee Corporation (CGC) / Husniyati Ali - Ali, Husniyati (2018)
The role played by the non financial institutions such as Credit Guarantee Corporation (CGC), has marked a new way for the entrepreneurs to get an access to financing, even without collateral. Significantly, with the introduction of Islamic Financing Guarantee Schemes, the entrepreneurs have better choice of financing, since it is free from riba and gharar, and is based on underlying productive economic activity, hence generate legitimate income and wealth. The Islamic financing guarantee scheme chosen in this study is Direct Access Guarantee Scheme (DAGS-i). A total of 42 firms are involved in this study, from years 2006 to 2014, with total observations of 378. Firms are being grouped under three industries; namely Logistic and Transportation, Construction and Engineering and Services. To what extend do the firms are efficient in using this scheme in their operation? Do they really achieve the cost, profit and revenues efficiencies? The Data Envelopment Analysis (DEA) has been employed to measure these efficiencies. The result indicates that Magna Prima Construction Sdn Bhd, Doyes Engineering Sdn. Bhd, Ecochaste Shipping Sdn Bhd, SAP Air Hitam Properties Sdn Bhd, and Redtone Technology Sdn Bhd are the most efficient firms. They have achieved the efficiencies scores of 1 of their cost, profit and revenue, throughout the period of observations. The other firms have to adjust their operations in order to be efficient and are advised to benchmark against the efficient firms. The study recommends that thorough monitoring and advising from CGC and peer assistance would help inefficient firm to improve and sustain in the industry, even towards creating a venture capital between the firms.